Classification of Emerging Scoliosis in Congenital Scoliosis After Hemivertebra Resection and Short Segmental Fusion - Chenkai Li; Xiaohan Ye; Bingtai Han; You Du; Yiwei Zhao; Dihan Sun; Shengru Wang; Jianguo Zhang (Orthopaedic Surgery)
Objective Emerging scoliosis (ES) is a rare phenomenon after hemivertebra (HV) resection and short segmental fusion. Since the introduction of the ES, there have been rare in‐depth studies. The aim of the present study was to further analyze the characteristics, risk factors, treatment, and prognosis of ES. Methods A retrospective study analyzed patients with congenital scoliosis due to a single HV who underwent posterior correction and short fusion from 2002 to 2022. ES was defined as a Cobb angle ≥20° from its initial value and an apical vertebra located ≥2 levels away from the fusion region. ES patients and non‐ES patients were matched at a 1:2 ratio. Both demographics and radiological parameters were compared. Univariate analysis and multivariate logistic analysis were used to identify the risk factors of ES. Results Among 261 patients, 13 patients (5.0%) experienced ES. There were eight females and five males. The mean age of the ES patients at the time of primary surgery was 6.6 ± 3.7 years old (2.0–13.2 years old), with a mean follow‐up of 64.2 ± 47.9 months (12–156 months). The ES could be further divided into three types: balance‐related ES, complication‐related ES, and separated ES. There were three balance‐related ESs, six complication‐related ESs, and four separated ESs. At the last follow‐up, six patients were under observation, six patients underwent brace treatment, and one patient underwent revision surgery. Multivariate logistic analysis showed that the magnitude of postoperative compensatory curve (CC) was an independent risk factor for ES (OR = 1.172, p = 0.014). Conclusions ES is an extraordinary phenomenon after HV resection and short fusion, and it can be divided into three types. The magnitude of postoperative CC was an independent risk factor for ES. According to the severity of ES, observation, brace, or surgery can be chosen.